The Effect Of Customer Friendship And Product Availability On Purchase Decisions At 5f Clothing Store, Batu Ajamu Market, Panai Hulu District - Futri Anggriani; Midrawati Hasibuan; Erni Manja Hasibuan (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study was to determine the significant or insignificant influence of customer friendliness and availability of goods on purchasing decisions at the 5F clothing store in Batu Ajamu Market, Panai Hulu District. The study used quantitative methods and an associative causality approach. The data collection technique used was through observation and interviews. The sample in this study was 99 respondents or consumers. The sampling technique was simple random sampling. The data analysis technique used statistical techniques/SPSS by conducting validity and reliability tests, then for the questionnaire and multiple linear regression analysis with the T Test and F Test to prove the hypothesis. The results showed that there was a close and significant influence of customer friendliness on purchasing decisions, there was no close and significant influence of the availability of goods on purchasing decisions, the influence of customer friendliness and availability of goods was 35.6% and the remaining 64.4% was influenced by other factors and variables.